DETERMINATION OF PERFORATED SURFACE PARAMETERS FOR FIBER MASS CLEANING FROM DUST IN AN AERODYNAMIC CLEANING MACHINE - Muhammad R. Sadikov; Alijon A. Yusupov; Sharipov Furqat Shavkat oʻgʻli; Mirzatillayev Abdulla Soxatillo o‘g‘li (Western European Studies, 2025)
This article explores the effective cleaning process of fibers from dust and debris using aerodynamic cleaning machines. The study presents results on the impact of perforated hole sizes, the discharge zone, and air velocity modes on technological processes. It demonstrates the potential to improve the efficiency of the cleaning process by determining the optimal hole diameter. These methods can be applied in the textile industry to enhance fiber quality and make production processes more efficient.
Keywords: aerodynamic cleaning machines; fiber cleaning; separation of dust and debris